Fluidization of fine coal particles in an ultrasound enhanced gas-solid fluidized bed - Sayuri Naicker; Neeraj Kuarsingh; Milan Carsky; David Lokhat (South African Journal of Chemical Engineering)
Coal continues to be one of the most important primary energy sources and is a major contributor to economic growth, especially in the developing world. Coal fines are an unavoidable by-product of coal extraction. Fine coal is classified as waste when it is too difficult or uneconomical to process and thus disposed of into waste ponds. This leads to environmental liability and loss of valuable high-quality product. There have been numerous studies regarding the efficient processing of fine coal particles, to realise the full economic potential whilst reducing the product's environmental risks. Fluidization is commonly used in the processing of powders or fine particles since it enables continuous powder handling and promotes good particulate mixing. However, the fluidization of fine particles is challenging due to the propensity for channelling, clustering and elutriation. Enhanced fluidization methods have been used to overcome these problems. Several methods that have been employed include electric or magnetic fields, mechanical vibrations, centrifugal forces, introduction of foreign particles, the use of microjets and the use of acoustic sound waves. This study considered the use of in-situ ultrasound as a new alternative enhanced fluidization technique. The overall aim of this research project was to quantitatively determine the improvement in the fluidization behaviour of fine coal particles, under the influence of ultrasound. This new technique helped prevent channel formation, and bed cracking, and improvement in fluidization regimes were observed. Decreasing minimum fluidization velocities were observed for increasing ultrasonic intensities, across various bed heights. The addition of the ultrasound correction factor was able to improve the prediction capability of the model that was developed for the minimum fluidization velocity. The reduction in minimum fluidization velocity shows promise for reduced energy consumption, and increased production throughput, of the fine coal particle processing industry. Overall the novel application of ultrasound improved the quality and operability of the fluidization of fine coal particles.